Climate change challenges and responses. (Quezon City Climate Change Information Center, 2000)
This two-part video presents an overview of climate change and how the Philipine government and civil society responded to this challenge by establishing the Climate Change Information Center at the Manila Observatory in Quezon City.
VHS.
Director, Philip B. Daffon Jr., Judy G. Uson ; writer, Joy V. Galvez ; produced by The Big Event Co. for the Foundation for Philippine Environment and the Climate Change Information Center in cooperation with the united States Agency for International Development.
Keywords: Climate Change Information Center; Global warming; Climatic changes -- Government policy